The unique relation between cambodian somatic symptom and syndrome inventory (cssi) items and functional impairment among adolescents in cambodia - Sareth, Khann (Đại học Quốc gia Hà Nội, 2020)
Cultural perceptions of distress are useful for clinical practice as they reflect the perceived realities of the individuals and groups within this society. Cultural idioms of distress may not involve exact symptoms or syndromes of psychopathology. Thus, the present study investigated the unique association of Cambodian Somatic Symptom and Syndrome ent and help seeking among Cambodian Inventory (CSSI) items with functional impairn adolescents.